2014
DOI: 10.1016/j.celrep.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A Distal Locus Element Mediates IFN-γ Priming of Lipopolysaccharide-Stimulated TNF Gene Expression

Abstract: SUMMARY IFN-γ priming sensitizes monocytes/macrophages to lipopolysaccharide (LPS) stimulation, resulting in augmented expression of a set of genes including TNF. Here, we demonstrate that IFN-γ priming of LPS-stimulated TNF transcription requires a distal TNF/LT locus element 8 kb upstream of the TNF transcription start site (hHS-8). IFN-γ stimulation leads to increased DNase I accessibility of hHS-8 and its recruitment of IRF1, and subsequent LPS stimulation enhances H3K27 acetylation and induces enhancer RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 42 publications
5
28
0
2
Order By: Relevance
“…Despite increased TNF secretion in heme-trained Mφ, we could not find a difference in H3K27ac levels at the TNF promoter after heme treatment compared to control cells by ChIP-qPCR which is in line with our finding that the pan-innate immune training signature observed in both heme and β-glucan exposed Mφ involves the upregulation of mechanisms for cytokine release. This is in agreement with recent findings by other authors who used a model of IFNγ-priming 49 . Increased TNF release was also unrelated to H3K27ac in the TNF promotor itself as IFNγ dependent modifications occur at a region 8 kb upstream of the TNF promotor 49 .…”
Section: /37supporting
confidence: 94%
See 1 more Smart Citation
“…Despite increased TNF secretion in heme-trained Mφ, we could not find a difference in H3K27ac levels at the TNF promoter after heme treatment compared to control cells by ChIP-qPCR which is in line with our finding that the pan-innate immune training signature observed in both heme and β-glucan exposed Mφ involves the upregulation of mechanisms for cytokine release. This is in agreement with recent findings by other authors who used a model of IFNγ-priming 49 . Increased TNF release was also unrelated to H3K27ac in the TNF promotor itself as IFNγ dependent modifications occur at a region 8 kb upstream of the TNF promotor 49 .…”
Section: /37supporting
confidence: 94%
“…This is in agreement with recent findings by other authors who used a model of IFNγ-priming 49 . Increased TNF release was also unrelated to H3K27ac in the TNF promotor itself as IFNγ dependent modifications occur at a region 8 kb upstream of the TNF promotor 49 . Additionally, it was shown that innate immune memory does not only depend on H3K27ac but also involves histone methylation 18,50 .…”
Section: /37supporting
confidence: 94%
“…Previous studies have shown that IFN-g synergizes with TLR ligands to activate macrophages (22,23,34). In light of our findings that TLR engagement triggered the production of IFN-g by Agexperienced T cells, we examined whether the amount of IFN-g produced was sufficient to support the activation of macrophages.…”
Section: Tlr-dependent Activation Of T Cells Augments Macrophage Respmentioning
confidence: 99%
“…The production of IFN-g during this bystander activation supports the immune response against unrelated infections (14,16). To achieve this cross-protection, innate immune cells like dendritic cells and NK cells are recruited to the site of infection (7,21), and macrophages and neutrophils become activated by IFN-g (8,22,23).…”
Section: Tlr-mediated Innate Production Of Ifn-g By Cd8mentioning
confidence: 99%
“…IFN-γ and STAT1 have been implicated in nucleosome remodeling and opening of chromatin (122). Recent genome-wide studies of human macrophages revealed that IFN-γ induced stable and coordinated recruitment of STAT1, IRF1, and associated histone acetylation to enhancers and promoters of genes that are synergistically activated by IFN-γ and LPS, such as TNF , IL6 , and IL12B (123, 124). Importantly, CRISPR-mediated deletion established the functional importance of IFN-γ-primed enhancer at the TNF locus.…”
Section: Epigenetics In Priming Macrophage Activation Statesmentioning
confidence: 99%